Cell-type and subcellular compartment-specific APEX2 proximity labeling reveals activity-dependent nuclear proteome dynamics in the striatum - V. Dumrongprechachan (Nature Portfolio, 2021)
Mapping neuronal proteomes with genetic, subcellular, and temporal specificity is a challenging task. This study uncovers proteome dynamics in two classes of striatal spiny projection neurons in the mouse brain using a genetically targeted APEX2-based proximity labeling approach.